2013
DOI: 10.1002/jaba.26
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis Screening for Problem Behavior Maintained by Automatic Reinforcement

Abstract: A common finding in previous research is that problem behavior maintained by automatic reinforcement continues to occur in the alone condition of a functional analysis (FA), whereas behavior maintained by social reinforcement typically is extinguished. Thus, the alone condition may represent an efficient screening procedure when maintenance by automatic reinforcement is suspected. We conducted a series of 5-min alone (or no-interaction) probes for 30 cases of problem behavior and compared initial predictions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(160 citation statements)
references
References 25 publications
6
143
2
1
Order By: Relevance
“…Like any functional analysis, the IISCA is not equipped to demonstrate control by automatic reinforcement contingencies. When an interview suggests control by automatic reinforcement, arrangement of a series of alone sessions is recommended (Querim et al, ); treatment is then implemented if problem behavior persists despite the absence of socially mediated contingencies (see, e.g., Potter, Hanley, Augustine, Clay, & Phelps, ). However, automatic reinforcement was never suspected for participants in the current study because all interviews suggested socially mediated contingencies.…”
Section: Discussionmentioning
confidence: 99%
“…Like any functional analysis, the IISCA is not equipped to demonstrate control by automatic reinforcement contingencies. When an interview suggests control by automatic reinforcement, arrangement of a series of alone sessions is recommended (Querim et al, ); treatment is then implemented if problem behavior persists despite the absence of socially mediated contingencies (see, e.g., Potter, Hanley, Augustine, Clay, & Phelps, ). However, automatic reinforcement was never suspected for participants in the current study because all interviews suggested socially mediated contingencies.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a traditional FA based on procedures described by Iwata et al (1982/) with modifications outlined by Fisher, Piazza, and Chiang () and Querim et al (). That is, we conducted a series of consecutive ignore sessions to determine whether problem behavior persisted in the absence of social contingencies as a test for automatic reinforcement (Querim et al).…”
Section: Methodsmentioning
confidence: 99%
“…We first conducted a Functional Analysis Screening Tool (Iwata, DeLeon, & Roscoe, 2013) with three members of the group home staff who worked with Carl each week to identify possible variables maintaining Carl's rumination. We then conducted a modified pre-treatment screening analysis (Querim et al, 2013) to determine if rumination occurred in the absence of social consequences. Our sessions were longer in duration than those used by Querim et al (2013).…”
Section: Methodsmentioning
confidence: 99%